Addressing the Physician Shortage in Hawai‘i: Recruiting Medical Students Who Meet the Needs of Hawai‘i's Rural Communities - Schiff, Teresa (University Clinical, Education & Research Associate (UCERA), 2012)
BACKGROUND: Past studies in the continental US have demonstrated that students from rural areas and those who go into primary care are more likely to practice in rural areas than urban-born and specialty physicians. METHODS: This study uses two separate data sets to examine whether medical students and young physicians in Hawai‘i follow the same pattern. A retrospective study of graduates of the University of Hawai‘i John A. Burns School of Medicine from 1993–2006 was performed examining the relationship between practice location and high school attended for those practicing in Hawai‘i. In addition, a survey was conducted with the first, second and third year medical students examining their practice intentions as related to where they grew up. Both data sets were analyzed using Chi Squared tests to determine the significance of associations between individuals from rural backgrounds practicing or intending to practice in rural areas. RESULTS: The relationship in both cases showed that students and physicians from rural areas were more likely to practice in rural areas. However, 81% of all respondents reported being willing to consider practicing in rural area, especially if lifestyle, work environment, and employment opportunities were favorable. DISCUSSION: If the State of Hawai‘i wants to expand the physician workforce in the rural areas of Hawai‘i, recruiting more students from rural areas and increasing desirability of rural practice settings are excellent paths to take.